"Cannot see? Use your strengths!" A randomized controlled trial of strengths intervention for improving self-esteem among visually impaired individuals. (October 2019) - Matsuguma, Shinichiro; Kawashima, Motoko; Sano, Fumiya; Tsubota, Kazuo
Objective: To evaluate the association between strengths use and self-esteem among visually impaired individuals in Study 1 and reveal the causal effect of a strengths intervention in Study 2. Design: A prospective cross-sectional design in Study 1 and a randomized controlled, open-label, parallel-group comparative design in Study 2. Setting: Several welfare institutions for visually impaired individuals in the Kanto area of Japan. Subjects: In Study 1, 59 participants with visual impairments (mean age = 49.34 ± 4.89 years, range = 22–82 years) were recruited. In Study 2, participants (mean age = 41.36 ± 12.09 years, range = 22–61 years) were recruited and randomly assigned to an intervention ( n = 11) or wait-list control group ( n = 11). Intervention: A strengths intervention was performed in Study 2. Main measures: In Study 1, we examined the association between Strengths Use Scale and Rosenberg Self-Esteem Scale scores. In Study 2, the primary outcome was the difference in change in Rosenberg Self-Esteem Scale scores from baseline to one-month follow-up between the groups. Results: In Study 1, simple and multiple regression analyses revealed that the Rosenberg Self-Esteem Scale score was significantly associated with the Strengths Use Scale score (β = 0.60, P < 0.001; β = 0.55, P < 0.001, respectively). In Study 2, we found a significant between-groups difference in the improvement in Rosenberg Self-Esteem Scale scores from baseline to one-month follow-up ( F (1, 19) = 18.61, P < 0.001). Conclusion: Utilizing psychological strengths might improve self-esteem among visually impaired individuals.